Pengaruh Etos Kerja Dan Budaya Kerja Terhadap Kinerja Karyawan Outsourcing Pada PT. Mega Armada Sudeco (Tunas Auction) Di Bekasi - Refa Dana; Aprilia Astuti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract The purpose of this study is to determine the effect of work ethic and work culture on the performance of outsourced employees at PT. Mega Armada Sudeco (Tunas Auction) in Bekasi. The research method used is a quantitative method with an associative approach. The sampling technique used is saturated sampling with a total of 75 respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results show that work ethic has a significant effect on the performance of outsourced employees with a coefficient of determination value of 79.7% and the hypothesis test results obtained show that the calculated t-value is greater than the t-table value (16.932 > 1.993). Work culture has a significant effect on the performance of outsourced employees with a coefficient of determination value of 13.3% and the hypothesis test results obtained show that the calculated t-value is greater than the t-table value (3.352 > 1.993). The results of the correlation analysis indicate that the relationship between work ethic and work culture is in the low category. Simultaneously, work ethic and work culture have a significant effect on the performance of outsourced employees with the regression equation Y = -1.190 + 0.874X₁ + 0.143X₂. The coefficient of determination value is 81.2%, while the remaining 18.8% is influenced by other factors outside this study. The simultaneous hypothesis test shows that the calculated F-value is greater than the F-table value (155.587 > 3.124)